Balconies as adaptable spaces in apartment housing - Terri Peters; Sepideh Masoudinejad (Buildings & Cities, 2022)
New requirements for living, working, and learning at home due to Covid-19 have highlighted two fundamental needs in apartment housing: (1) 'adaptability' to fit multiple functions in a limited area; and (2) access to 'private outdoor space' to support residents’ health and wellbeing, and to provide spatial and thermal variety in small units. The two needs may initially appear to be disconnected: when residents have a high demand for flexibility and adaptability in apartment housing, balconies tend to be overlooked as potential spaces to facilitate adaptability. An analysis of several international housing projects with innovative balcony designs and unit designs is the basis for the identification of several typologies of balconies. Typologies of adaptable balconies and examples are used to show how they may support housing adaptability within a dwelling. The ‘adaptable balcony’ concept is introduced in the context of multifamily housing design, together with a clear definition of active and passive adaptability by inhabitants.   'Practice relevance' Apartment balconies are often overlooked as design elements capable of influencing housing adaptability. This paper explores how adaptable balconies could support and improve residents’ functional use of their dwellings. The ease of adaptability, how and to what degree residents can adapt their balcony spaces, are shown in built examples. The ‘adaptable balcony’ concept in the context of multifamily housing can provide developers, designers, and inhabitants with an enhanced, more flexible use of domestic spaces. Several typologies of adaptable balconies are identified and considered for how they may support housing adaptability within a dwelling. Two notions of passive and active adaptability in balcony design can help designers facilitate the desired levels of adaptability in a project.